(untitled) (Journal of Oriental Studies, 2018)
More than 95% of cargo freight between China and Europe are shipped by maritime mode. The increase of the overloads and extension of leading time of the shipments make the participants of international trade and global logistic sector to seek for new routes of transportation. In the last decade the land bridge via Kazakhstan (Dostyk station) has been confirming its sustainable development. Contemporarily about three container trains daily run between different locations along the corridor between China and Europe. The given corridor has a potential for further development, because the western regions of China are developing within the framework of “Go West” program, which will positively influence on the increase of trade and shipments.